THE FACTORS AND REASONS FINANCIAL BUDGET INSOLVENCY OF MUNICIPAL ENTITIES IN CURRENT CONDITIONS - Y. Orlova (Publishing House of the State University of Management, 2018)
As a result of the theoretical provision’s studying the financial insolvency of municipalities, financial and budgetary flows at the municipal level are systematized, the factors influencing the financial and budgetary condition of municipalities are identified, and the reasons for the formation of insolvent territories are formulated. It was concluded that municipalities is lacked sufficient revenues to fulfill powers and there is a low level of budget autonomy. This is based on the analysis of local budget’s indicators. The obtained results can be used to develop the main directions for improving municipal financial relations and to determine ways of solving the financial problems.